Expression of IL-10 and TGF-β1 in horses experimentally infected with T. equi merozoites is associated with antibody production but not modulation of pro-inflammatory responses - Onzere, Cynthia K.; Bastos, Reginaldo G.; Bishop, Richard P.; Suarez, Carlos E.; Fry, Lindsay M. (Frontiers in Immunology, 2024)
Theileria equi (T. equi) is an apicomplexan parasite that causes severe hemolytic anemia in equids. Presently, there is inadequate knowledge of the immune responses induced by T. equi in equid hosts impeding understanding of the host parasite relationship and development of potent vaccines for control of T. equi infections. The objective of this study was to evaluate the host-parasite dynamics between T. equi merozoites and infected horses by assessing cytokine expression during primary and secondary parasite exposure, and to determine whether the pattern of expression correlated with clinical indicators of disease. Our findings showed that the expression of pro-inflammatory cytokines was very low and inconsistent during both primary and secondary infection. There was also no correlation between the symptoms observed during primary infection and expression of the cytokines. This suggests that the symptoms might have occurred primarily due to hemolysis and likely not the undesirable effects of pro-inflammatory responses. However, IL-10 and TGF-β1 were highly expressed in both phases of infection, and their expression was linked to antibody production but not moderation of pro-inflammatory cytokine responses.